Sensitivity of strength reduction factor for structures considering soil-structure interaction. (May 2022) - Anand, Vishwajit; Satish Kumar, S.R.
Abstract: The conventional perception of soil-structure interaction being ever-beneficial to seismic response of structures has been challenged by evidences of damages inflicted on built infrastructure by a number of earthquakes. Numerical studies by many researchers have also revealed the possible detrimental effects of soil-structure interaction. It has been recently established that this uncertainty stems from two conflicting phenomena, viz. reduction of elastic seismic demand owing to elongated natural period and enhanced damping, and lowering of strength reduction factor. While the first phenomenon lowers the seismic demand and is therefore beneficial, the second phenomenon is detrimental likely to increase the seismic demand. Over the last decade, a number of researchers have estimated strength reduction factor for structures considering soil-structure interaction effects. This paper attempts to assess sensitivity of strength reduction factor to variations in a number of non-dimensional parameters. These parameters are related to geometrical and material properties of structure, foundation and soil. It is found that lowering of strength reduction factor is most sensitive to stiffness contrast between structure and soil. It is also observed that structures with large expected inelasticity tend to afford a much-lowered strength reduction factor. The effect of other factors is found to be comparatively little or insignificant.